ADVANCED APPLICATIONS OF PET/CT IN VISUALIZING TUMOR SPREAD IN BREAST CANCE (Herald of the National Children's Medical Center, 2025)
Breast cancer (BC) remains one of the leading causes of cancer morbidity and mortality among women. Accurate staging of the tumor process at the time of initial diagnosis is one of the key factors determining treatment success. In recent years, the introduction of positron emission tomography with ¹⁸F-fluorodeoxyglucose (¹⁸F-FDG PET/CT) has significantly expanded diagnostic capabilities in oncology. This molecular imaging method makes it possible not only to determine the localization and metabolic activity of the tumor but also to detect distant and occult metastases that are inaccessible to traditional imaging methods such as ultrasound, MSCT, and MRI.